Household and agro-waste upcycling into sustainable unbreakable artworks and furniture pieces by eco-friendly organic chemical reactions - Mai Magdy Abdelrazeq (Multidisciplinary Adaptive Climate Insights)
Millions of tons of agrowaste and household waste are generated that end up in landfills, which in turn affect human health. Waste has serious impacts on the environment throughout the greenhouse gas emissions. Waste is a huge economic burden on governments and distort the civil and aesthetic appearance. The invention converts waste into crystallized capsule by eco-friendly organic chemical reaction. Secondly, the capsule undergoes a covering by a second chemical reaction to form the final product which is artwork or furniture pieces that are sustainable and unbreakable. The final product can be manufactured in a large scale, since the raw materials are affordable and available.     Received on, 15 January 2025 Accepted on, 10 April 2025 Published on, 05 May 2025